Bone Scaffolds: An Incorporation of Biomaterials, Cells, and Biofactors - Bahraminasab, Marjan; Janmohammadi, Mahsa; Arab, Samaneh; Talebi, Athar; Nooshabadi, Vajihe Taghdiri; Koohsarian, Parisa; Nourbakhsh, Mohammad Sadegh (ACS biomaterials science & engineering, 2021)
Large injuries to bones are still one of the most challenging musculoskeletal problems. Tissue engineering can combine stem cells, scaffold biomaterials, and biofactors to aid in resolving this complication. Therefore, this review aims to provide information on the recent advances made to utilize the potential of biomaterials for making bone scaffolds and the assisted stem cell therapy and use of biofactors for bone tissue engineering. The requirements and different types of biomaterials used for making scaffolds are reviewed. Furthermore, the importance of stem cells and biofactors (growth factors and extracellular vesicles) in bone regeneration and their use in bone scaffolds and the key findings are discussed. Lastly, some of the main obstacles in bone tissue engineering and future trends are highlighted.